Morpho-molecular analysis of podolampadacean dinoflagellates (Dinophyceae), with the description of two new genera. Issue 2 (4th March 2023) - Mertens, Kenneth Neil; Carbonell-Moore, M. Consuelo; Chomérat, Nicolas; Bilien, Gwenael; Boulben, Sylviane; Guillou, Laure; Romac, Sarah; Probert, Ian; Ishikawa, Akira; Nézan, Elisabeth
ABSTRACT: Sequences were obtained for 58 podolampadacean single cells from France, Reunion Island (French territories) and Japan (6 SSU rDNA only, 40 SSU+LSU and 12 LSU only). The sequenced taxa belong to five of the eight described genera: Podolampas, Blepharocysta, Lissodinium, Gaarderiella and Mysticella . Two new genera, Alatosphaera and Pseudalatosphaera, were erected to accommodate ' Blepharocysta ' hermosillae and ' Blepharocysta ' denticulata . Most genera are well supported by concatenated LSU–SSU rDNA phylogenies, with the least support for Lissodinium . Metabarcoding of podolampadaceans using the V4 region of SSU rDNA showed a resolution too low to discriminate genera or species. Roscoffia and Cabra are here considered podolampadaceans, whilst Lessardia is considered to belong in a separate family. The relationship of Rhinodinium to the Podolampadaceae needs further study. Desmoschisis was recorded for the first time in Alatosphaera and Pseudalatosphaera . Several ribotypes need further study to attribute a species name to them.